Differences in the reading performance of Texas grade 4 boys enrolled in Title I, part A and non-Title I, part A schools: A multiyear analysis - Rodriguez, Dawn; Slate, John R (Journal of Interdisciplinary Studies in Education, 2024)
In this investigation, the reading performance of Texas Grade 4 boys was compared by their enrollment or non-enrollment in Title I, Part A schools. Data were obtained from the Texas Education Agency Public Education Information Management System for all Grade 4 boys in Texas who took the State of Texas Assessment of Academic Readiness assessment in the 2016-2017, 2017-2018, and 2018-2019 school years. Inferential statistical analyses revealed the presence of statistically significant differences in all three school years. Boys enrolled in non-Title I, Part A schools outperformed boys enrolled in Title I, Part A schools in all three Reading Reporting Categories and in all three grade level standards. Recommendations for research and implications for policy and practice are suggested.